Solving the Many Problems with Inner City Jobs - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2000)
Inner-city business development is often proposed as a solution to inner-city poverty. However, research evidence suggests that creating new jobs in the inner city is unlikely by itself to significantly increase the employment or earnings of the inner city poor. Public subsidies for inner city business development may be justified by greater environmental, congestion, and fiscal benefits of inner city vs. suburban business location decisions. The research evidence suggests that some boost in inner city business development may be provided by a combination of economic development incentives with enhanced public services. A different set of policies must be used to increase the earnings of the inner city poor. These employment solutions to inner city poverty should include two components; (1) creating more effective labor market intermediaries to make it easier for inner-city residents to find good jobs and for employers throughout the metropolitan area to find good inner city workers; (2) enhancing the job skills of the inner-city poor, particularly their "soft skills", by training programs that have closer ties to employers and incorporate subsidized employment experience. Given the magnitude of the poverty problem, any realistic policy to significantly reduce inner-city poverty through enhanced earnings will require tens of billions of dollars of annual government spending.
Keywords: J4; I3; 330; wages; inner city; earnings; poverty; welfare; labor demand; Bartik